The genus Perlomyia Banks in Taiwan (Plecoptera: Leuctridae) - Sivec, Ignac (Illiesia, 2012)
Three previously unrecognized species of Perlomyia Banks are described from Taiwan and compared to others in the genus. New taxa include P. angulata sp. n., P. excavata sp. n. and P. taiwanensis sp. n.
Keywords: entomology; Leuctridae; Perlomyia; Plecoptera; Taiwan; new species